Analisis Pengaruh Tingkat Pendidikan Orang Tua dan Disiplin Belajar Terhadap Prestasi Belajar Siswa - Moslimah (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
External factors such as the family environment, especially the level of parental education, and internal factors such as student learning discipline, have a significant role in determining the level of student learning success. This study aims to analyze the influence of parents’ educational level and students’ learning discipline on academic achievement. This research employed a quantitative approach with a population consisting of all sixth grade students at Madrasah Ibtidaiyah Raudhatul Ulum Pematang Rambai, totaling 45 students. The sampling technique used was total population sampling, consisting of 24 students from class VI-A and 21 students from class VI-B. Data were collected using a questionnaire, while data analysis was conducted using SPSS for Windows version 25. The results of the regression analysis showed an R Square value of 0.516, indicating that parents’ educational level (X1) and students’ learning discipline (X2) contributed 51.6 percent to students’ academic achievement (Y). The effective contribution of variable X1 was 2.77 percent, while X2 contributed 48.83 percent. Therefore, it can be concluded that parents’ educational level and students’ learning discipline have a positive influence on improving the academic achievement of sixth grade students at Madrasah Ibtidaiyah Raudhatul Ulum Pematang Rambai.